Resposta :
Resposta:
A)27
B)32
C)87
D)8
E)60
F)30
G)5
H)10
Explicação passo a passo:
[tex]A) 23 + X = 50\\X = 50 - 23\\X = 27\\\\B) 82 - X = 50\\-X = 50 - 82\\-X = -32\\-X * -1 = -32 * -1\\X = 32\\\\C) X - 37 = 50\\X = 50 + 37\\X = 87\\\\D) 2 + 6X = 50;\\6X = 50 - 2\\X = \frac{48}{6}\\X = 8\\\\E) X - \frac{20}{2} = 50\\X - 10 = 50\\X = 50 + 10\\X = 60\\\\F) (X - 5) * 2 = 50\\X - 5 = \frac{50}{2}\\X - 5 = 25\\X = 25 + 5\\X = 30\\\\G) 2 * X * 5 = 50\\10X = 50\\X = \frac{50}{10}\\X = 5\\\\H) \frac{90}{X} + 41 = 50\\\frac{90}{X} = 50 - 41\\\frac{90}{X} = 9\\90=9X[/tex]
[tex]\frac{90}{9}=X\\X = 10[/tex]
basta realizar a operação inversa o que está se pedindo
a) 50 - 23 = a 27
b) 82 - 50 = 32
c) 50 + 37 = 87
d) 2 + 6 . 8 = 50
e)60 - ( 20/2)=50
f) (30 - 5) . 2 =50
g) 2 . 5 . 5 =50
h) ( 90/9) + 41 = 50